Un linaje enfrentado por el poder: don Francisco Temamascuicuil y don Pedro Solcuatzin, caciques de Iztacamaxtitlan, siglo XVI - Lidia E. Gómez García (Nuevo mundo - Mundos Nuevos, 2011)
At the beginning of the Colonial period, once Tenochtitlan had been conquered, the main scenario for political struggle and power legitimization among Indian elites were Spanish institutions. The Indian strategy was centered around restoring former power structures within the new Colonial regime. This required an extensive internal process of negotiation and adaptation. However, this process did not necessarily presented coherent and clear positions on either the Indian or the Spanish representation. On the contrary, in some cases this process confronted Indian nobility to the point of division and the inevitable destruction of their lineage, which lead to the creation of a new elite associated with the Spanish regime. Such is the case of Temamascuicuil´s lineage, an otomí cacique of the ancient Iztacamaxtitlán Kinship. This article means to show the political strategies by which two nobel Indians from the same lineage were confronted by power struggles.